2013
DOI: 10.1093/jjco/hyt055
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Breast MRI in the Management of Ductal Carcinoma In Situ Diagnosed on Needle Biopsy

Abstract: Needle-biopsy-proven ductal carcinoma in situ cases with non-mass-like enhancement type might be sufficiently managed using breast magnetic resonance imaging features such as enhanced lesion size and signal intensity, incorporating the number of cancer-cores at needle biopsy specimen in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…On the other hand, our finding that the sensitivity of MRI is too low to be of use in identifying patients with occult breast cancer is in contrast with several studies that concluded that it is possible to use MRI to detect some of the occult breast cancers, without attempting to determine the sensitivity of MRI in doing this [9,12,13,15,16]. In studies of Goto et al and Harowitz et al, the sensitivity of MRI was presented as ROC curves with an AUC of 0.71 and 0.719, respectively, [10,14], which is in line with our finding of an AUC of 0.73.…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, our finding that the sensitivity of MRI is too low to be of use in identifying patients with occult breast cancer is in contrast with several studies that concluded that it is possible to use MRI to detect some of the occult breast cancers, without attempting to determine the sensitivity of MRI in doing this [9,12,13,15,16]. In studies of Goto et al and Harowitz et al, the sensitivity of MRI was presented as ROC curves with an AUC of 0.71 and 0.719, respectively, [10,14], which is in line with our finding of an AUC of 0.73.…”
Section: Discussioncontrasting
confidence: 64%
“…We found a predominance of nonmass enhancement as a feature of ADH as well as DCIS. Our rate of non-mass enhancement among DCIS is in the upper limit of the 70%-80% rate of nonmass enhancement encountered in MR studies designed for diagnosing or excluding invasive disease in patients with DCIS diagnosed by means of imageguided biopsy (30)(31)(32)(33).…”
Section: Multivariate Analysismentioning
confidence: 83%
“…When planning a surgical strategy for treating preoperatively diagnosed cases of DCIS, it is clinically important to be able to more accurately predict the presence or absence of unexpected invasive disease in surgical specimens [28].…”
Section: Discussionmentioning
confidence: 99%